2016
DOI: 10.15845/ntvp.v1i1.997
|View full text |Cite
|
Sign up to set email alerts
|

The first-year as a mentor in Norwegian teacher education – asking for the authoritative word

Abstract: Abstract:In this article I describe and interpret how a first-year mentor for student teachers, Anna, lacks support in her new role within the context of field practice in Norwegian teacher education. Even though she is employed at what is called a "practice school", she feels alone in her work with the student teachers. There is no one there to answer her questions on how to perform her new role. I argue that due to the lack of an arena where she can discuss her questions, Anna positions herself as someone wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…While earlier studies (e.g. Nilssen, 2016) have found that school-based mentors feel loneliness in their jobs as mentors, this study's findings showed that almost all participants felt they belonged to a professional community in the OTPD programme, which seems to have motivated them in their professional development. Motivation and satisfaction are indeed closely connected, and Andreasen et al (2019) claim that job satisfaction is important for teachers in the start-up phase.…”
Section: Being Part Of a Communitycontrasting
confidence: 88%
See 3 more Smart Citations
“…While earlier studies (e.g. Nilssen, 2016) have found that school-based mentors feel loneliness in their jobs as mentors, this study's findings showed that almost all participants felt they belonged to a professional community in the OTPD programme, which seems to have motivated them in their professional development. Motivation and satisfaction are indeed closely connected, and Andreasen et al (2019) claim that job satisfaction is important for teachers in the start-up phase.…”
Section: Being Part Of a Communitycontrasting
confidence: 88%
“…Butler and Cuenca (2012) describe the situation for new school-based mentors as a “sink-or-swim approach” (p. 35), where the teacher education institution leaves them alone to discover what to do by themselves. This aligns with other studies presenting teachers as insecure in their role as a school-based mentor (Bullough, 2005; Nilssen, 2016).…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations